A Comparative Assessment of Scars Resulting From Skin Grafts in Facial Defects. Issue 1 (January 2022) - Seo, Du-Heon; Shin, Jin Yong; Roh, Si-Gyun; Chang, Suk Choo; Lee, Nae-Ho
Abstract : Purpose: The authors compared facial scars after split-thickness skin grafts (STSGs) performed with a dermal substitute or after full-thickness skin grafts (FTSGs) in facial defect. Materials and Methods: The medical records of patients who had undergone FTSG or STSG with dermal substitute after skin cancer surgery between March 2016 and December 2018 were retrospectively reviewed. The scars resulting from skin grafts were assessed using the patient and observer scar assessment scales (PSAS and OSAS) in our clinic after a minimum of 6 months postoperatively. Results: Of the 50 study subjects, 35 patients (FTSG group) received FTSG only and 15 patients (STSG group) received STSG with the dermal substitute. The total scores of PSAS and OSAS were significantly lower in the FTSG group and it is suggested that both patients and observers thought that better scar outcomes were achieved when FTSGs were used. However, for defects smaller than 1.8 cm 2 and defects located in the periorbital area, there was no statistically significant difference in the scores of PSAS and OSAS in the 2 groups. Interestingly, for defects located in the periorbital area, although there was no significant difference, PSAS and OSAS scores were lower in the STSG group than in the FTSG group. In other word, scar outcomes in the STSG group were better. Conclusions: Although there was no significant difference, unlike what we usually know, our result shows that STSG with dermal substitute tended to produce comparable or rather better results than FTSG under some conditions. Abstract : Supplemental Digital Content is available in the text